Removal of trace nonylphenol from water in the coexistence of suspended inorganic particles and NOMs by using a cellulose-based flocculant. (October 2016) - Yang, Zhen; Ren, Kexin; Guibal, Eric; Jia, Shuying; Shen, Jiachun; Zhang, Xuntong; Yang, Weiben
Abstract: A flocculation method was used for the removal of trace nonylphenol (NP) from synthetic surface water containing natural organic matters (humic acid, HA) and suspended inorganic particles (kaolin). A polymeric flocculant (CMCND), with enhanced cationic property and unique switchable hydrophobic/hydrophilic characteristic, was specially designed for this application. CMCND showed a high efficiency for trace NP removal, turbidity and UV254 abatements: under optimized conditions (pH: 4; T: 35 °C; dosage: 40 mg/L), the removal of NP reached up to 79%. By using dosage-pH flocculation diagrams and correlation analyses as tools, kaolin and HA were found to exert synergistic effects on NP removal, with the aid of CMCND; the synergistic effect of HA is higher due to π-π stacking. Zeta potential-dosage profiles clearly demonstrated charge neutralization predominated at pH 4, due to the strong cationic groups in the flocculant. Floc size monitoring displayed that the delayed phase transformation process (from hydrophilicity to hydrophobicity) of CMCND at 35 °C enhanced NP removal. In addition, spectral analyses clarified the interactions among CMCND, NP, kaolin and HA: charge attraction and hydrophobic interaction between CMCND and NP played the key roles. The findings are of significance for removing endocrine-disrupting chemicals in environmental remediation. Graphical abstract: Highlights: CMCND has enhanced cationic properties and switchable hydrophobicity/hydrophilicity. It has a high efficiency for trace NP removal, turbidity and UV254 abatements. Dosage-pH diagrams and correlation analyses show synergistic effects of HA and kaolin. Floc size monitoring shows CMCND's delayed phase transformation enhances NP removal. Charge attraction and hydrophobic interaction predominate between CMCND and NP.